The effect of socio-economic status on severity of periocular basal cell carcinoma at presentation. - Lim, Lik Thai; Agarwal, Pankaj K.; Young, David; Yann, Elliott Ah-Kee; Diaper, Charles J. M. (University of Strathclyde Glasgow, 2015)
To evaluate the influence of socio-economic factors on size of periocular basal cell carcinoma (BCC) at presentation. METHODS: All periocular basal cell carcinoma (BCC) cases receiving treatment from the oculoplastics team in South Glasgow Hospitals NHS Trust, Glasgow between 1999 and 2009 were identified retrospectively. Information collected included demographic details of patients, side and site of lesions, type of lesions and size of lesions. The size of lesion is defined as small for any dimension not exceeding 5mm, medium for dimensions between 6mm-10mm and large for dimensions exceeding 11mm. Home address was used to determine the Scottish Index of Multiple Deprivation (SIMD) rank. The demographics, size of lesion and SIMD rank were investigated using the general linear regression modelling.